Comparative study of the ideal and actual adhesion interfaces of the die bonding structure using conductive adhesives. Issue 1 (2nd January 2022) - Tsurumi, Naoaki; Tsuji, Yuta; Baba, Taiki; Murata, Hiroyuki; Masago, Noriyuki; Yoshizawa, Kazunari
ABSTRACT: A die bonding interface consisting of a plated gold surface and conductive silver paste was investigated using two approaches: One was a computational method for the ideal interaction, while the other was an experimental technique to get some ideas about the actual bonding. A density functional theory (DFT) calculation was employed to clarify the adhesive interface between the Au (1 1 1) surface and bisphenol-A type epoxy resin which included dicyandiamide as a curing agent. The computational results showed that the cyano group involved in the hardener strongly binds to a gold atom on the ideal surface. This interaction is likely to be assigned to σ-donation and π-back donation. The predicted adhesive strength was 1.15 GPa. To evaluate the real adhesion strength, small-sized single lap-shear joints were fabricated and tensile shear tests were performed. The measured adhesive stress was about 27 MPa. The results of surface analytical methods indicated that the actual die pad surface was not smooth. Furthermore, an altered layer terminated with Au(CN)x was found on the top of the die pad. It was inferred that the mechanism of the actual die bonding interaction would be changed to the formation of hydrogen bonds. This could be a reason why reduced adhesive strength was observed.